2014
DOI: 10.3892/ijo.2014.2584
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced apoptosis by pemetrexed and simvastatin in malignant mesothelioma and lung cancer cells by reactive oxygen species-dependent mitochondrial dysfunction and Bim induction

Abstract: Abstract. Pemetrexed is a multitarget antifolate currently used for the treatment of malignant mesothelioma and non-small cell lung cancer (NSCLC). Statins, 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors used primarily for hyperlidpidemia, have been studied for their antiproliferative and pro-apoptotic effects. However, the effects of simvastatin on pemetrexed-induced apoptosis have not been investigated. In this study, we investigated whether combination treatment with pemetrexed and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Simvastatin was shown to induce caspase-dependent apoptosis in A549 cells which is regulated by the Bcl2 family proteins and ROS and can be reversed by treatment with N-acetylcysteine4647. Other investigators have reported that simvastatin can induce apoptotic pathways in A549 and H460 cells by blocking the cell cycle and down-regulating cyclin D1 and cyclin dependent kinases (CDKs) expression4849.…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin was shown to induce caspase-dependent apoptosis in A549 cells which is regulated by the Bcl2 family proteins and ROS and can be reversed by treatment with N-acetylcysteine4647. Other investigators have reported that simvastatin can induce apoptotic pathways in A549 and H460 cells by blocking the cell cycle and down-regulating cyclin D1 and cyclin dependent kinases (CDKs) expression4849.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination of lovastatin and valproate was shown to reduce cell invasion of Acc-Meso-1, a human-derived MPM cell line [110]. HWANG et al [51] reported a synergistic effect of the combination of pemetrexed and simvastatin on apoptosis induction in MSTO-211 MPM cells by reactive oxygen [43] Inhibition of angiogenesis [44] Inhibition of invasion and metastasis [45] Induction of tumour differentiation [46] Reversion of multidrug resistance [47] Phase III: gastric cancer [48], colorectal cancer [49] Phase III: ongoing in SCLC [50] Preclinical [47,[51][52][53] Itraconazole Antifungal Induction of angiogenesis [54] Inhibition of hedgehog pathway [8] Phase II: NSCLC [55] Prostate cancer [56] Basal cell carcinoma [57] Preclinical [58] Arsenic trioxide Preclinical [52,85,88] Thalidomide Sickness in pregnant females (withdrawn) [29] Inhibition of angiogenesis [31] Inhibition of cell proliferation [32] Immunomodulatory function [33] FDA approved: multiple myeloma [34] Phase III [37] Anisomycin Antibiotic Induction of apoptosis [89] Preclinical [90] Preclinical [90]…”
Section: Statinsmentioning
confidence: 99%
“…Pemetrexed induces caspase-dependent and -independent apoptosis in human melanoma cells through intracellular ROS accumulation, which in turn promotes DNA damage [ 169 ]. In MM cell lines, pemetrexed induced ROS production and caspase-dependent apoptosis [ 170 ]. To the best of our knowledge, no previous study has investigated on ROS production in mesotlelioma cells upon pemetrexed and cisplatin combination treatment.…”
Section: Introductionmentioning
confidence: 99%